F(x) = 1/(x+2) & g(x) = x/(x-3)
(f(x) + g(x) = 1/(x+2) + x/(x-3). Reduce to same denominator:
1/(x+2) + x/(x-3) =(x-3) + x(x-3)/(x+2).(x-3) ==> (x²+3x-3)/(x+2).(x-3)
The result of simplifying each number (-3)¹/₃ . (-3)¹/₃ . (-3)¹/₃ using the exponent rules is -3
To solve this exercise we have to resolve algebraic operations following the exponent rules.
(-3)¹/₃ . (-3)¹/₃ . (-3)¹/₃
Using the product rule that indicates that: the exponent result will be the addition of these exponents, we have:
(-3)¹/₃⁺ ¹/₃ ⁺ ¹/₃
(-3)³/₃
(-3)¹
-3
<h3>What is an exponent?</h3>
In mathematics an exponent is the number of time that a number, called (base) is multiplied by itself. It is also called, power or index.
Example: 3² = 3*3 = 9
Learn more about exponent at: brainly.com/question/847241
#SPJ4
There are several important information's already given in the question. Based on those information's the answer to the question can be easily deduced.
Number of cups of Oatmeal
required by Aunt Bess for making 6 dozen cookies = 3
Then
Number of cups of oatmeal
required by Aunt Bess for making 1 dozen cookies = (3/6)
= 1/2
So
Number of cups of oatmeal
required by Aunt Bess for making 18 dozen cookies = (1/2) * 18
= 9 cups
So Aunt Bess will require 9 cups of oatmeal for baking 18 dozen cookies. I hope the procedure is clear enough for you to undestand.
x = 5i x =-5i
Step-by-step explanation:
x^2+25=0
Rewriting
x^2 - (-25)=0
Writing as the difference of squares
a^2 - b^2= (a-b) (a+b)
where a = x and b = (sqrt(-25)) =±5i
( x-5i) ( x+5i) =0
Using the zero product property
x-5i =0 x+5i =0
x = 5i x =-5i
Answer:
16.6
Step-by-step explanation:
Add the numbers together.
13.2+20=33.2
Now divide the number by 2.
33.2/2=16.6
Hope this helps!
If not, I am sorry.